The Effect of Pre-Service EFL Teachers’ Deeper Learning Awareness on the 21st-Century Skills Promotion - Sukarno, Sukarno; Pratiwi, Dwiyani (Journal of English Culture, Language, Literature and Education, 2025)
The current study aims to investigates the effect of pre-service EFL teachers' awareness of promoting deeper learning on students’ 21st-century skills encouragement. This quantitative research uses a cross-sectional survey design. The participants were 366 pre-service EFL teachers from five universities in the Special Region of Yogyakarta, Indonesia. The data were collected by distributing two questionnaires: the Deeper Learning Awareness, adapted from Jiang (2022) and Rodriguez and Fitzpatrick (2014), and the 21st-Century Skills questionnaires, adapted from Kelley et al. (2019). The pilot testing, expert judgement and SPPS analysis were used to assess the questionnaires’ validity, reliability, and practicality. The data were analyzed using Regression Analysis. The result reported that pre-service EFL teachers in the Special Region of Yogyakarta are aware of promoting deeper learning to support students’ 21st-century skills. Their deeper learning awareness also significantly predicted the promotion of 21st-century skills. The more pre-service EFL teachers are aware of promoting deeper learning, the more the 21st-century skills are implemented in the EFL learning.